Cellular and molecular studies of Marfan syndrome mutations identify co-operative protein folding in the cbEGF12-13 region of fibrillin-1. - Whiteman, P; Willis, A; Warner, A; Brown, J; Redfield, C; Handford, P (2007)
Human fibrillin-1 is an extra-cellular matrix glycoprotein with a modular organisation that includes 43 calcium-binding epidermal growth factor-like (cbEGF) domains arranged as multiple tandem repeats interspersed with transforming growth factor beta binding protein-like (TB) domains. We have studied Marfan syndrome-causing mutations which affect calcium binding to cbEGF13, and demonstrate that in human fibroblast cells they cause unexpected endoplasmic reticulum retention, indicative of a folding defect. Biochemical and biophysical studies of in vitro refolded fragments from the TB3-cbEGF14 region indicate long-range and unidirectional effects of these substitutions on the adjacent N-terminal domain cbEGF12. In contrast, only short-range effects of a pathogenic mutation affecting calcium binding to cbEGF19 are observed, and secretion of this mutant protein occurs. Further NMR studies on wild-type cbEGF12-13 and cbEGF12-14 identify a co-operative dependence of domain folding where calcium binding to cbEGF13 is required before cbEGF12 can adopt a native Ca(2+)-dependent fold. These data demonstrate that during biosynthesis of fibrillin-1, multiple tandem repeats of cbEGF domains may not necessarily fold independently and therefore missense mutations resulting in identical substitutions may have different effects on the fate of the mutant protein. Complex folding of modular proteins should therefore be considered when interpreting the molecular pathology of single-gene disorders.